Pengaruh Gaya Kepemimpinan dan Jabatan Fungsional Terhadap Karir ASN Melalui Motivasi Sebagai Variabel Intervening pada Sekretariat Daerah Kota Solok - Irawati, Sisri; Aima, Havidz; Lusiana , Lusiana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of leadership style and functional position on ASN careers through motivation as an intervening variable at the Solok City Regional Secretariat. The method used is multiple linear regression analysis and path analysis, with a sample of 70. The results of the study obtained a significant influence of leadership style on motivation at the Solok City Regional Secretariat. There is an insignificant influence of functional position on motivation at the Solok City Regional Secretariat. There is a significant influence of leadership style on ASN careers at the Solok City Regional Secretariat. There is a significant influence of functional position on ASN careers at the Solok City Regional Secretariat. There is a significant influence of motivation on ASN careers at the Solok City Regional Secretariat. Motivation is able to mediate the influence of leadership style on ASN careers at the Solok City Regional Secretariat. Motivation has not been able to mediate the influence of functional positions on ASN careers at the Solok City Regional Secretariat. Finally, the author suggests to the Solok City Regional Secretariat to further improve its leadership style because it has the most dominant value of its influence on ASN careers at the Solok City Regional Secretariat